Dispersal: triggers, traits, and fitness consequences in common voles (Microtus arvalis) - Hahne, Jörg (2009)
It is widely accepted that dispersal plays a major part in population dynamics as well as in population genetics. Still, dispersal and its associated consequences constitute a big gap in our knowledge, which is mainly due to the difficulties in obtaining robust field data. In this study we used an experimental approach in semi-natural enclosures with individually marked common voles, Microtus arvalis. We combined classical capture-mark-recapture studies with molecular analyses to ascertain what proximate factors emigration trigger, and investigated morphological characteristics of dispersers as well as a potential genetic predisposition for the dispersal behavior. Males predominantly emigrated prior to the maximum population densities (i.e. as presaturation dispersers) and their dispersal rate was positively correlated with density increase. This surely enhances the success of male dispersers in finding reproductively active mates and still vacant sites to settle. The dispersal rate of females was associated with the proportion of residents in a population indicating that the propensity of females to disperse is dependant on social interactions. The male-biased dispersal rate and the relative high proportion of natal dispersers supported the inbreeding avoidance hypothesis. Based on the trapping history and reproductive state, three groups of voles were differentiated. Residents, defined as mature and stationary individuals, were the heaviest and reproductively most successful individuals. Philopatrics were stationary voles but never reached sexual maturity. They comprised the lightest individuals. While philopatric females might participate in nursing or defense against intruders, males may wait to sneakily mate as soon as the more competitive residents are absent or die. Male dispersers predominantly delayed the onset of reproduction and accelerated maturation at the time of emigration. This surely decrease agonistic interactions with residents in the natal population. Female dispersers showed a high dichotomy ...